Application of tip-flexible vacuum-assisted ureteral access sheath in flexible ureteroscopic laser lithotripsy for renal stones in a child after pyeloplasty: a case report - Qiang Cheng; Jianwei Cao; Lin Zhang; Qiaolin Chen; Houwei Lin (Frontiers in Pediatrics)
ObjectivesTo explore the application of tip-flexible vacuum-assisted ureteral access sheath-assisted retrograde intrarenal stone surgery/flexible ureteroscopic lithotripsy in children.Patients and methodsA retrospective analysis was conducted on the clinical data of a pediatric patient who developed kidney stones following pyeloplasty for congenital ureteropelvic junction obstruction. The child underwent tip-flexible vacuum-assisted ureteral access sheath-assisted retrograde intrarenal stone surgery under general anesthesia. Inpatient records and postoperative follow-up results were collected.ResultsThe kidney stones were utterly removed, and there were no complications like infection, bleeding, or secondary obstruction. Moreover, there was no significant damage to the anastomotic site after pyeloplasty.ConclusionThe use of tip-flexible vacuum-assisted ureteral access sheath-assisted flexible ureteroscopic lithotripsy is safe and effective for pediatric lithotripsy.